The music of what happens : poems, poets, critics - Vendler, Helen Hennessy (Cambridge, Mass. : Harvard University Press, 1988)
A collection of essays in which Helen Vendler examines the function of literary criticism, different critical methods and styles, and the impact criticism has on poets and their work.
Includes index.
Reprints of articles originally published 1976-1987.
Adult
Keywords: American poetry -- 20th century -- History and criticism; English poetry -- 20th century -- History and criticism; Poetry; American poetry -- History and criticism; English poetry -- History and criticism; Poetry